Kajian Evaluasi Kelayakan Bangunan Gedung PLN UPL Praya - Muhammad Taqiudin; Yuliani Budi Permata Sari; Faeruzza Athiya; Dunung Waskito Aji; Lalu Sulthonul Azmi (Universitas Kristen Indonesia Toraja, 2026)
A building feasibility evaluation study is an important step to ensure the safety, comfort, and sustainability of building functions, especially in public service facilities. This activity was carried out at the PLN ULP Praya office building, Central Lombok Regency, West Nusa Tenggara, which has been operating since 1985. The purpose of this study was to determine the level of building feasibility based on structural, architectural, utility, safety, and health aspects of the building. The methods used included visual inspection, field measurements, hammer tests, and analysis of the condition of building elements based on building feasibility inspection standards. The inspection results showed that the building suffered severe damage characterized by foundation subsidence, large cracks in the walls, reinforcement corrosion, concrete peeling, and damage to the roof frame. The structural strength value obtained was below the construction feasibility standard so that the building was declared structurally unfit for function. Although several supporting aspects such as lighting, drainage, and sanitation systems still functioned quite well, the damaged condition of the main structure has the potential to endanger the safety of users. Therefore, rebuilding the building structure is recommended as the safest solution to ensure the safety, stability, and sustainability of the building's function in the future.